SOSIALISASI TERAPI MENGGENGGAM BOLA KARET UNTUK MENINGKATKAN KEKUATAN OTOT PADA PASIEN STROKE NON HEMORAGIC DI PUSKESMAS PURWAKARTA - Wirdan Fauzi Rahman; Sherly, Sherly; Wulan Audia (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Stoke is one type of disease that causes disability and death. One of the problems that arise is the weakening of muscle strength in the extremities and will hinder activities in meeting daily needs. This application uses a case study method of applying a handheld rubber ball which is carried out at least 2 times a day for 5 days. The subject used was 1 patient who was diagnosed with stroke with hemiparase. The results of the application showed that after being given the application of rubber ball gripping therapy for 5 days the muscle strength of the upper left extremity increased as measured by the Handrip Dynamometer before application was 4.1 kg and after application it became 6.4 kg and when measured using a manual muscle strength tester. The respondent's muscle strength in grade 2 experienced a slight change but remained within the range of grade 2 muscle strength. The application of grasping a rubber ball showed that it was proven to increase muscle strength in stroke patients who experienced hemiparase. Stroke patients who experience hemiparase are expected to be able to do handheld rubber ball therapy to increase extremity muscle strength